3, 3′‐Dinitrophenolsulphonephthalein: an acid–base indicator dye with unusual properties. (13th December 2016) - Mchedlov‐Petrossyan, Nikolay O.; Laguta, Anna N.; Shekhovtsov, Sergey V.; Eltsov, Sergey V.; Cheipesh, Tatyana A.; Omelchenko, Irina V.; Shishkin, Oleg V.
Abstract : This paper is devoted to the phenolsulphonephthalein nitro derivative 3, 3′‐dinitrophenolsulphonephthalein, also called nitrophenol violet (NPV). The neutral molecular form, H2 R, was isolated as a sultonic tautomer, and an X‐ray crystal structure analysis was carried out. UV‐vis absorption spectra in methanol, DMSO, acetonitrile, and water at different pH values were ascribed to the molecular and anionic (H2 R, HR −, and R 2− ) species. Whereas the p K a values of this acid–base indicator (HR − ⇆ R 2− + H + ) in water and DMSO are close to those of 3, 3′, 5, 5′‐tetrabromophenolsulphonephthalein (or bromophenol blue), replacing the four Br atoms with two NO2 groups results in a pronounced tendency to carbinol formation. In weakly acidic aqueous media, the HR − anion slowly converts into the colourless carbinol H2 ROH − . The latter is transformed to the orange carbocation only in concentrated (70–94 wt%) sulphuric acid. The formation of H2 ROH − is atypical for the common sulphonephthalein indicators and should be ascribed to the enhanced positive charge density on the nodal carbon atom. The reaction mechanism and kinetic equation explaining this pH‐dependent process are proposed, in addition to a kinetic study of the common process R 2− + HO − → ROH 3− in the alkaline region. The numerical characterisation of the protolytic processes obtained for NPV is also helpful in gaining a better understanding of the properties of previously studied 3, 3′, 5, 5′‐tetranitrophenolsulphonephthalein, which is much less accessible for a quantitative description.